A framework tool for conceptualizing integrated water resources for sustainable water management. Issue 1 (13th September 2022) - Borden, Carter; Goodwin, Peter
Abstract: As the pressures on water resources are ever increasing, the organization of complex disparate data and scientific information to inform the actions to protect and enhance the resilience of freshwater resources is key for sustainable development and implementation of integrated water resource management (IWRM). Methodologies supporting IWRM implementation have largely focused on water management and governance, with less attention to evaluation methods of ecologic, economic, and social conditions. To assist in assessing water resource sustainability, the Integrated Hydro‐Environment Assessment Tool (IHEAT) has been developed to create a framework for different disciplines and interests to engage in structured dialogue. The IHEAT builds on the considerable body of knowledge developed around IWRM and seeks to place this information into a single framework that facilitates the cogeneration of knowledge between managers, stakeholders, and the communities affected by management decisions with the understanding that there is a need to merge expert analysis with traditional knowledge and the lived experience of communities. IHEAT merges the driver‐pressure‐state‐impact‐response (DPSIR) framework, the Millennium Ecosystem Assessment's ecosystem services and human well‐being (HWB) framework, sustainability criteria for water resource systems, and water resources indexes and sets of indicators to better understand spatiotemporal interactions between hydrologic, socioeconomic, and ecologic systems and evaluate impacts of disturbances on ecological goods and services and HWB. IHEAT consists of a Conceptual Template (IHEAT‐CT) which provides a systematic framework for assessing basin conditions and guiding indicator selection as well as an Assessment Interface (IHEAT‐AI) for organizing, processing, and assessing analytical results. The IHEAT‐CT, presented herein, is a rapid screening tool that connects water use directly, or through ecosystem goods and services (EGS), to constituents of HWB. Disturbance Templates for eight pressure types, such as land‐use change, climate change, and population growth, are provided to guide practitioners regarding potential changes to landscape elements in the hydrological cycle, impacts on EGS, and societal implications on HWB. The basin screening results in a summary report card illuminating key freshwater ecosystems, the EGS they provide, and potential responses to drivers and pressures acting on the hydrologic system. This screening provides a common understanding by technical and nontechnical parties and provides the foundation for more complex conceptual models should they be required. An indicator list guides the selection of hydrologic, ecologic, economic, and social analytical methods to support IWRM technical input. Abstract : To assist in assessing water resource sustainability, the Integrated Hydro‐Environment Assessment Tool (IHEAT) has been developed to create a framework for different disciplines and interests to engage in structured dialogue. IHEAT merges the driver‐pressure‐state‐impact‐response (DPSIR) framework, the Millennium Ecosystem Assessment framework, sustainability criteria for water resource systems, and water resources indexes and sets of indicators to better understand spatiotemporal interactions between hydrologic, socio‐economic, and ecologic systems and evaluate impacts of disturbances on ecological goods and services and human well‐being. The IHEAT‐CT (Conceptual Template) is a rapid screening tool that connects freshwater ecosystems to water use through ecosystem goods and services providing technical and nontechnical parties a shared understanding and the foundation for more complex conceptual models.